Please help with this problem
![Please help with this problem class=](https://us-static.z-dn.net/files/dc7/e55c60e195a557444ae53802a4816d19.png)
Answer:
(d) ∞
Step-by-step explanation:
The expression can be simplified to one that is not indeterminate:
[tex]\dfrac{(1+x)^{24}}{x}-\dfrac{1}{x}=\dfrac{(1+x)^{24}-1}{x}=\dfrac{1+24x+\dots+24x^{23}+x^{24}-1}{x}\\\\=\dfrac{24x+\dots+24x^{23}+x^{24}}{x}\\\\=24+\dots+24x^{22}+x^{23}[/tex]
A polynomial with a positive leading coefficient will tend to infinity as x goes to infinity.